Statistical analysis of the probability of interaction of globular clusters with each other and with the galactic center on the cosmological time scale according to Gaia DR2 Data - Ishchenko, Marina; Sobolenko, Margaryta; Berczik, Peter; Panamarev, Taras (Kinematics and physics of celestial bodies, 2023)
This study is aimed at investigating the dynamic evolution of the orbits of stellar globular clusters (SGCs). To integrate the orbits backward in time, the authors use models of the time-varying potentials derived from cosmological simulations, which are closest to the potential of the Galaxy. This allows for estimating the probability of close passages (“collisions” herein) of SGCs with respect to each other and the Galactic center (GC) in the Galaxy undergoing dynamic changes in the past. To reproduce the dynamics of the Galaxy in time, five of the 54 potentials previously selected from the IllustrisTNG-100 large-scale cosmological database, which are similar in their characteristics (masses and dimensions of the disk and halo) to the current physical parameters of the Milky Way, are used. With these time-varying potentials, we have reproduced the orbital trajectories of 143 SGCs 10 billion years back in time using our original φ-GPU high-order N-body parallel dynamic computer code. Each SGC was treated as a single physical particle with the assigned position and velocity of the cluster center from the Gaia DR2 observations. For each of the potentials, 1000 initial conditions were generated with randomized initial velocities of SGCs within the errors of the observational data. In this study, we consider close passages to be passages with a relative distance of less than 100 pc and a relative speed of less than 250 km s-1. Clusters that pass at longer distances and/or with higher velocities do not have a substantial dynamic effect on the orbits of SGC. In our opinion, the largest changes in the orbits of clusters can be caused by clusters that pass with low velocities at distances smaller than several fold (for example, fourfold) the sum of the radii of the cluster half-masses. Therefore, the authors regard such close passages separately (for brevity, we will call such passages “collisions”). To select clusters that pass at close distances from the GC, the following criterion is applied based only on the relative distance: it must be less than 100 pc. Applying the above criteria, the authors obtained statistically significant rates of close passages of SGCs with respect to each other and to the GC. It has been determined that SGCs during their evolution have approximately ten intersecting trajectories with each other on the average and approximately three to four close passages near the GC in 1 billion years at a distance of 50 pc for each of the chosen potentials.
Gesehen am 13.06.2023